The emergence of a knowledge-intensive sector in Portugal: social networks and innovation in the software sector - Salavisa, I. (2012)
This paper deals with the development of the software for telecommunications sector, a relatively small segment in the global software industry though one of its most innovative. In fact, its products address the demand of one of the most sophisticated and fastest changing industries today, the telecommunications industry. We attempt to explain how and why this sector has evolved in Portugal since its inception in the early 1980s. Social networks have played a relevant role in this entrepreneurial and innovative process, both for the formation and early stage development of firms. We will analyse the relevance and type of the networks involved in the process, before investigating the existence of an association between their composition and the innovative patterns of the firms, in terms of more radical versus more incremental innovation. This implies taking into account the intra-sector diversity, namely the existence of distinct groups of firms within the sector, in relation to their innovative strategies and capabilities. Finally, we will draw some conclusions and discuss policy implications.